Measuring work-role transitions: The cross-cultural experience of hotel expatriates in Malaysia - Halim, Haslina; Mustaffa, Che Su; Azizan, Farah Lina (SEARCH Journal 2020, 2020)
The literature on expatriation highlighted many individuals and organisational factors that affect expatriate adjustment. However, the roles of some individual and organisational factors are still not clear and have been ignored by past researchers. Thus, the purpose of this paper is to investigate the variations in expatriates’ work, general and interaction adjustment and to examine the relationship between work-role characteristics and expatriate adjustment in the hotel industry. The work-role characteristics; which are comprised of role novelty, role ambiguity and role conflict, are tested on the different dimensions of adjustment. Self-administered questionnaires were distributed to 323 respondents who were comprised of expatriates working in Malaysia’s hotel industry. The findings revealed a positive correlation between role novelty and work adjustment that indicated the impact of work-role characteristics on adjustment dimensions. However, both role ambiguity and role conflict are negatively correlated with work adjustment. The findings from this study proved significant for the industry as it contributes towards new knowledge on expatriation in a multicultural society, especially the work adjustment of hotel expatriates. It would also help create awareness among hotel companies on the importance of work characteristics in the process of adjustment. The findings also contributed to new empirical findings in regards to literature on expatriation and cross-cultural adjustment, which integrate the information on determinants of adjustment among hotel expatriates. Beside the findings, the discussions on limitations and suggestions for future research are also presented in the paper.